Association between dipeptidyl peptidase‐4 inhibitors and urinary tract infection in elderly patients: A retrospective cohort study. Issue 8 (30th May 2018) - Imatoh, Takuya; Nishi, Takumi; Yasui, Midori; Maeda, Toshiki; Sai, Kimie; Saito, Yoshiro; Une, Hiroshi; Babazono, Akira
Abstract: Purpose: Dipeptidyl peptidase‐4 (DPP‐4) inhibitors are a new class of antidiabetic drugs. Although they have been reported to increase the risk of infection, the findings are controversial. Given that urinary tract infections (UTIs) are common in the elderly, we conducted a retrospective cohort study by using health care insurance claims data, to elucidate the association between the DPP‐4 inhibitors and the incidence of UTI in latter‐stage elderly patients. Methods: We analyzed 25, 111 Japanese patients aged 75 years and older between the fiscal years 2011 and 2016. Patients using DPP‐4 inhibitors and sulfonylureas (SUs) were matched at a 1:1 ratio using propensity scoring. The Incidence rate ratio (IRR) of UTI was compared between users of SUs and users of DPP‐4 inhibitors by Poisson regression. Moreover, subgroup analyses stratified by sex were conducted to evaluate whether the combination of prostatic hyperplasia and DPP‐4 inhibitors is associated with the incidence of UTI in male patients. Results: The use of DPP‐4 inhibitors was associated with an increased risk of UTI (adjusted IRR 1.23, 95% CI [1.04‐1.45]). After propensity score matching, the association remained significant (adjusted IRR 1.28, 95% CI [1.05‐1.56]). Moreover, elderly male patients with prostatic hyperplasia who received DPP‐4 inhibitors had a higher risk of UTI than SU users without prostatic hyperplasia (Matched: crude IRR 2.90, 95% CI [1.78‐4.71]; adjusted IRR 2.32, 95% CI [1.40‐3.84]). Conclusions: The long‐term use of DPP‐4 inhibitors by elderly patients, particularly male patients with prostatic hyperplasia, may increase the risk of UTI.